COP 26 -- The Road to Where? (Global Journal of Management and Business Research, 2021)
Who would have thought that after almost 30 years since the UN Convention on Climate Change, the gap between goals and delivery on them remains so wide, and that consequently global warming continues unabated? Clearly, the current approach to the issue has one major flaw: it doesn#x2019;t work. At this rate, the goals of the international agreements cannot be met. The recent COP meeting (which annually monitors progress), represented for the first time a welcome (albeit timid) dose of realism. Gone were the all-too-frequent rhetorical pronouncements about the dangers to humanity, and the self-congratulatory declarations celebrating the new promises to avert such a disaster. There was moderate recognition that the world was on the way to a dangerous rise of 2.7#xB0;C towards global warming, while experts estimate that the outlined plans could produce a somewhat lower trajectory. Consequently, the target in the original agreements of 1.5#xB0;C is still in force, but barely, and it has therefore been agreed to review the commitments by the end of 2022 to steer plans to meet the agreed targets. An effort of this dimension requires a change of historical proportions for energy policies and an unprecedent level of investment calling for a profound transformation in production and transportation practices, investments in renewable energy, new technologies, efficiency, as well as carbon capture and storage. It will have to be recognized that most of the energy demand (and CO2 emissions) will be generated by the associated economic growth in emerging economies (especially in Asia), and that the early stages of economic development tend to be energy intensive. Hydrocarbons (which replace human and animal toil by internal combustion engine). Thus, most of the attention will have to be focused outside the OECD, which will constitute the largest share of energy growth. This will require better attention in (i) the institutional and economic policy implications, given the less developed organizational and governance capacities in these regions; (ii) a sharper focus on economy, efficiency, effectiveness, and simplicity, in view of the limited human and financial resources in those countries; and (iii) the mobilization of knowledge and inventiveness of the private sector to develop new technologies and more commercial approaches than those existing to date, to respond effectively and with results on the ground. To #x201C;level the playing field#x201D; between traditional and renewable energy sources, the cost of emissions will have to be recognized, subsidies to traditional sources discontinued, and the multiplicity of allocated funds that distort and unnecessarily complicate the allocation of resources will have to be avoided. Whatever the formula to establish carbon prices (from taxes or Carbon Frontier Adjustment Mechanisms proposed by the European Union), until a free and a functioning carbon market can operate, a more forceful and rapid change of the energy matrix can take place, with the necessary slack to have solutions that will take time, without negatively affecting societies that cannot face the changes with the speed and cost that arise in the short term.
Keywords: climate change conference of the parties (COP); carbon dioxide emissions (CO2)